2008
DOI: 10.1063/1.2964788
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement of Thickened Liquids Used for the Management of Dysphagia

Abstract: Abstract. Dysphagia is a condition where a person has difficulty in swallowing. This can lead to reduced dietary intake, dehydration and malnutrition and also aspiration of material into the lungs and asphyxiation. Using thickened fluids slow the act of swallowing and by doing so enhance safe swallowing. A common method of thickening drinks is to use a powdered thickener, but this can lead to problems in ensuring that the consistency of the degree of thickening appropriate to an individual is maintained by tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…Several manufacturers have stopped the production of starch based thickener due to many limitations that have been found. It was found that starch based thickeners have a long standing time; that is, it keeps thickening even after ten minutes of standing after mixing (Nicholson et al, 2008). Nevertheless, several manufacturers use a mixture of modified maize starch, guar gum and xanthan gum as their main ingredients.…”
Section: Modified Maize Starchmentioning
confidence: 99%
See 4 more Smart Citations
“…Several manufacturers have stopped the production of starch based thickener due to many limitations that have been found. It was found that starch based thickeners have a long standing time; that is, it keeps thickening even after ten minutes of standing after mixing (Nicholson et al, 2008). Nevertheless, several manufacturers use a mixture of modified maize starch, guar gum and xanthan gum as their main ingredients.…”
Section: Modified Maize Starchmentioning
confidence: 99%
“…This is because there are many factors that affect the ability to reliably produce thickened liquids with a consistent thickness level (Pelletier, 1997, Mills, 2008. These factors include a lack of knowledge about preparing thickened fluids, (Rosenvinge and Starke, 2005), differences in the behaviour of thickening agents , Sopade et al, 2008a, Sopade et al, 2008b, Garcia et al, 2005, solids content of the liquid (Sopade et al, 2008a) and differences in dispersing media , Garcia et al, 2005, Nicholson et al, 2008) amongst other parameters.…”
Section: Thickened Fluidsmentioning
confidence: 99%
See 3 more Smart Citations